Perceptions of Black millennials in public and private schools about the mix of rewards offered in the schools - Zata, Catherine; Ama, Njoku Ola (Eximia, 2024)
This study explored the perceptions of the millennial teachers on how they can be motivated, attracted and retained in teaching in public and private schools. Adopting the quantitative research design and the stratified random sampling method, data were collected from 215 millennials drawn from public and private schools in Johannesburg North with a structured questionnaire. The studied found that extrinsic rewards remained the preferred rewards by the millennials. They were extremely dissatisfied with the basic remunerations, performance management rewards, career growth and advancement, opportunities for development in the schools. Although they were significantly motivated to take up teaching by basic pay and bonuses, to retain them in teaching required opportunities for development, career growth and advancement, and good relationships in the schools. The study recommended developing policies and best practices by Ministry of Education on mix of rewards to attract and retain qualified Millennials into teaching and enhance teacher commitment.